The effect of product substitution on non-boundary inventory levels - Cevahir, Cihan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Competitive business world makes it difficult for companies to have high customerloyalty. As the number of manufacturer companies in markets gets higher, customersexpect higher service level from these manufacturers. If a company wants to keep the customer satisfaction level high, it must present products to customers on the time andplace customers desire. Stock out cases have become nightmares for companies especiallyin recent years. Inventory management and production control are two topics that carefulattention must be paid in related decision making processes. In this thesis, studies are focused on this problem. A system with random yields and two different product classes istaken into consideration. A model is developed that simplifies the decision makingprocesses related to production control and inventory management. In this model, productsubstitution method is applied at boundary and non-boundary states. Lost sales cost and substitution costs are valid in this model so that the difficulties manufacturers face insatisfying demands have been adapted to the model. Downward substitution is applied atboundary and non-boundary states both while upward substitution is applied only atboundary states. To simplify the decision making process, a methodology is presented that provides threshold values for production and substitution decisions. In addition, a simplermodel with only downward substitution at boundary states is used to test our model. Byrunning these two models under same parameter values, profit improvements that areobtained by applying the model developed in this research are observed.
Keywords: Inventory control.; Production control.